Impact of dose fractionation regimen of adjuvant radiotherapy on cosmetic outcomes after immediate breast reconstruction - Zh. V. Bryantseva; S. N. Novikov; D. G. Ulrikh; P. V. Krivorotko; I. A. Akulova; T. S. Yaganova; T. T. Tabagua; K. Yu. Zernov; A. M. Belyaev (Сибирский онкологический журнал, 2025)
Background. Evidence for the safety of using the hypofractionation (HF) regimen after immediate breast reconstruction (IBR) in patients with breast cancer is not well documented. the purpose of the study was a retrospective analysis of surgical treatment with IBR and postoperative radiation therapy (RT) in conventional fractionated (CF) and hypofractionated (HF) regimens in breast cancer patients. Material and Methods. a retrospective analysis of treatment outcomes was carried out in 219 breast cancer patients who underwent mastectomy with IBR using permanent implant or tissue expander. all patients received postoperative RT: 97 received CF RT (22–25 fractions of 2 Gy) and 122 HF RT (15–16 fractions of 2.66–2.7 Gy). Cosmetic complications were represented by reconstructive failure (RF). all patients underwent an analysis of the incidence of reconstructive failures (RF) or capsular contracture (CC) (Baker III–IV). Results. CF RT was performed in 97 women: 55 – after IBR using tissue expander and 42 using permanent implant. the median follow-up time was 61 months. Complications were observed in 37 women (35.1 %): RF in 22 cases (22.7 %) and CC in 12 (12.4 %) cases. the median time to RF was 8 months, CC – 48.5 months. after RT to the tissue expander, CC rate was 0 %, RF – 25.5 %. after RT to the implants, CC was revealed in 28.6 %, RF in 19 % cases. In patients who received HF RT, cosmetic complications were detected in 51 (41.8 %) of 122 patients. the median follow-up time was 34 months. RF was revealed in 22.1 % cases, the median time was 9 months. CC was observed in 24 women (19.7 %) with the median time of 27 months. after HF RT to the expander, CC was observed in 4.9 %, RF in 39 % of cases. After RT to the implant, CC was detected in 27.2 %, RF in 13.6 % of cases. no significant differences in the risk of complication between patients who received conventional or hypofractionated RT were found (р=0.19). after RT to the expander, no differences (р=0.18 and р=0.12). After RT to the implant, there were also no differences in the frequency of CC and RF (р=0.52 and р=0.42). Conclusion. There were no significant differences in the frequency of cosmetic complications after postoperative radiotherapy in conventional fractionation or moderate hypofractionation regimens.